2011
DOI: 10.1186/1472-6785-11-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hunger on the acoustic individuality in begging calls of a colonially breeding weaver bird

Abstract: BackgroundIn colonially breeding birds, the ability to discriminate between individuals is often essential. During post-fledging care, parents have to recognize their own offspring among many other unrelated chicks in the breeding colony. It is well known that fledglings and food-provisioning parents of many bird species use contact calls to convey their identity. These calls are also often used as hunger-related signals of need in young birds. Here, we investigate how such calls incorporate signals of need an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
1
25
1
Order By: Relevance
“…Nestling individual discrimination was significantly higher in a food‐deprived than food‐satiated state (36% of success vs. 31%). This is consistent with a previous study in Jackson's golden‐backed weavers ( Ploceus jacksoni ) showing that chicks were more easily identifiable statistically when begging in a hungry than in satiated state (Reers & Jacot, ). Using the same argumentation as above, this finding is not surprising.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nestling individual discrimination was significantly higher in a food‐deprived than food‐satiated state (36% of success vs. 31%). This is consistent with a previous study in Jackson's golden‐backed weavers ( Ploceus jacksoni ) showing that chicks were more easily identifiable statistically when begging in a hungry than in satiated state (Reers & Jacot, ). Using the same argumentation as above, this finding is not surprising.…”
Section: Discussionsupporting
confidence: 92%
“…Because the next prey item is highly valuable for hungry nestlings and they invest more effort in calling than food‐satiated nestlings, they would derive more benefits from being identified as motivated competitors to be given the priority to the prey. Alternatively, the change in discriminability with hunger level could be a nonadaptive by‐product, due to the fact that nestlings’ motivation is more variable when food‐satiated, and they signal at maximal and stable level when food‐deprived (Reers & Jacot, ). This argument does not apply to the barn owl, as we showed that the acoustic features signalling hunger level (such as call duration) present similar within‐individual repeatability when food‐deprived and food‐satiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mockingbird nests, Screaming Cowbird nestlings are rapidly outgrown by their larger host nest-mates and are thus expected to be hungrier than in Baywing nests and to compete more strongly to secure sufficient provisioning (De M arsico & Reboreda 2008). In other passerine species, deprived nestlings increase call duration, bandwidth or frequency modulation as their hunger level increases (Leonard & Horn 2006, Marques et al 2008, Reers & Jacot 2011, but see Anderson et al 2010). These observations accord with prior experimental work showing that Screaming Cowbird nestlings deprived of food increase the intensity of their begging displays as deprivation time increases (Lichtenstein 2001) and are more consistent with begging effort by Screaming Cowbirds as a signal of hunger rather than need (Mock et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We used Sound Analysis Pro (SAP) (for details see Tchernichovski et al 2000, Tchernichovski and Mitra 2004) to measure the following nine call features (see Table 1 for descriptions) of the first 25 calls on each recording that were free of background noise (total of 610 calls from 60 nestlings, mean ± SD 10.2 ± 5.8 calls/nestling, range: 1–25 calls/nestling): 1) duration of call part (in ms); 2) variance of amplitude modulation (in ms −1 ); 3) mean frequency (in Hz); 4) mean frequency modulation (°); 5) variance of frequency modulation (°); 6) mean entropy; 7) variance in entropy; 8) mean pitch (in Hz) and 9) mean pitch goodness. These features have been previously shown to be important in acoustic signatures, showing considerable variation across songbird nestlings (Jacot et al 2010, Reers and Jacot 2011, Reers et al 2011).…”
Section: Methodsmentioning
confidence: 97%